2020
DOI: 10.4274/imj.galenos.2019.59354
|View full text |Cite
|
Sign up to set email alerts
|

Are ABO Blood Groups and Rh Factor Risk Factors for Hypertensive Diseases of Pregnancy?

Abstract: Amaç: Çalışmamızın öncelikli amacı gebeliğin hipertansif hastalıkları (GHH) ile kan grupları arasındaki ilişkiyi incelemektir. İkincil amacımız ise GHH'lerin gelişiminde rol oynayan risk faktörlerini belirlemektir. Yöntemler: Kesitsel, gözlemsel ve prospektif olarak planlanan çalışmamıza 15-49 yaş arası gebeler dahil edildi. Gebeler iki gruba ayrıldı. Grup 1 (n=266), GHH nedeniyle yoğun bakım ünitesine kabul ettiğimiz hastalar; grup 2 (n=402), gebelik süresince herhangi bir komplikasyon gelişmeyen ve normotans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In another study by Phaloprakarn et al study on 5320 pregnant women, the researchers found that both A and AB blood types were significantly associated with risk of preeclampsia [7]. However, in the study published by Uzundere et al involving 668 pregnant women, AB0 blood group was not strongly associated with any hypertensive disease of pregnancy [8].…”
Section: Preeclampsiamentioning
confidence: 92%
See 1 more Smart Citation
“…In another study by Phaloprakarn et al study on 5320 pregnant women, the researchers found that both A and AB blood types were significantly associated with risk of preeclampsia [7]. However, in the study published by Uzundere et al involving 668 pregnant women, AB0 blood group was not strongly associated with any hypertensive disease of pregnancy [8].…”
Section: Preeclampsiamentioning
confidence: 92%
“…Many scientists have studied the relationship between AB0 blood group and preeclampsia, but their results are contradictory. For this reason, many scientists are still looking for conclusive results on the risk and predictive factors of this condition [5][6][7][8]. Two different types of preeclampsia are described based on the time of onset of the disease symptoms -early and late-onset preeclampsia.…”
Section: Preeclampsiamentioning
confidence: 99%